La asignación de los recursos públicos para subsanar el déficit de vivienda de interés prioritario en Bogotá (2012)
In this paper raises the issue of social housing in the city of Bogota and how public policy can contribute to more efficient resource allocation program to address the housing shortage, the paper reviews the various policies housing in Colombia and other countries in order to expose the qualities, strengths and weaknesses and their applicability in the case of Bogota.